Using of the Supporting Awareness Program to Increase the Productivity of Wheat Crops During the Covid 19 Pandemic of Anbar Province/Iraq - saleh, Jasim; Ibrahim, Ahmed Mahmood; Ghaffoori, Anwer Thamer (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
The COVID-19 pandemic has had a major impact on agricultural production. One of the most important strategic crops for agricultural production is wheat, which is of great importance to food security in general and is even included in the foreign policies of countries. Iraq seeks to increase the productivity of wheat crops by spreading the awareness program that supports the wheat crop. The study was conducted in the villages of (Kusaiba and Abu Flies) with a total number of (55 farmers), in Anbar province. Used the SPSS program to analyze the data. The results of the study showed that the majority of farmers under 45 years of age were 70.2%. As for educational attainment, most farmers had only or less primary education at a rate of 61.4%, and the majority of farmers were married, 84.2%. In addition, most farmers have had their lands for decades and renters 83%, . In the field of agricultural sources, their sources came from the Internet by 54.4%, and in the field of agricultural problems and obstacles, the problem of the delay in receiving the marketing amount, as to the effects of Covid 19, the most agreeable was the distance of the health centers from the villages. The relationship was significant with age, marital status, educational attainment, and land ownership at a significant level of 0.05. The researcher recommends that farmers should be encouraged to educate, also the necessity of providing support for agricultural requirements and providing a suitable environment for the agricultural market.